A Systematic Review on the Performance Characteristics of Sustainable, Unfired Admixed Soil Blocks for Agricultural and Industrial Waste Management. (6th October 2021) - Sharma, Tarun; Singh, Sandeep; Singh Thind, Parteek; Singh Chohan, Jasgurpreet; Kumar, Raman; Sharma, Shubham; Kaplonek, Wojciech; Khalilpoor, Nima; Issakhov, Alibek
Abstract : Unfired admixed soil blocks are composed of standard soil and a stabilizer or reinforcement material in the form of binder and fiber. This literature review systematically examines the performance characteristics of unfired admixed soil blocks made by using binders such as cement, lime, and other agricultural and industrial wastes available in the form of fibers and ash. A systematic search was carried out on Web of Science and SCOPUS using different keywords, and 313 records were found. After the screening and eligibility process as per PRISMA guidelines, 36 papers were eligible and hence selected to be reviewed and analyzed. This paper examines the performance characteristics of the blocks in terms of physical properties, mechanical properties, durability, microstructural evaluation, statistical analysis, cost analysis, energy consumption, and carbon dioxide emission. It was found that of the total 9 parameters considered for discussion, most of the studies using different admixtures (binder and fibers) in soil blocks were focused on compressive strength testing of blocks, water absorption, and durability by wetting drying cycles. However, other parameters like bulk density, maximum dry density and optimum water content, thermal conductivity, tensile strength, and flexural strength examined in recent studies are also reported in this paper. This systematic review proposes some research problems to be worked on various additional parameters like linear shrinkage, pull out test, erosion test, sorptivity test, porosity, efflorescence, water permeability, freeze/thaw test, and analysis of energy consumption and carbon dioxide emissions during the manufacturing of unfired admixed soil blocks using various binders and fibers for further study which the current literature lacks.